Oral B / Muhammad Farhan Md Ismail - Md Ismail, Muhammad Farhan (2021)
This case study project is one of the essential assignments for the Technology Entrepreneurship (ENT600) Course, which aims to teach students how to be entrepreneurs who use technology in their businesses and how to operate their businesses. As a result, Oral B was selected as the company for this case study. Oral B aspires to be the most famous tooth brush in the world. It also had a demand for tooth brushes in Malaysia. As a result, a concise outline of the company's facts and goods is created based on internet analysis. In addition, this report provides a detailed overview of the company's sales, marketing, and operational strategies. Finally, the company's SWOT analysis, which included strengths, weaknesses, opportunities, and threads, is covered. The company's challenge is outlined in the swot analysis, and recommendations for improving and solving the issues are suggested.